Wujud Patrimonialisme di Taman Ismail Marzuki, 1968-1998 - Yusuf, Nur Fadilah (Universitas Gadjah Mada, 2024)
This article discusses the forms of patrimonialism that occurred during the New Order era with a case study of Taman Ismail Marzuki. The state's involvement in hegemony in the field of culture transforms into Javanese power politics present in the post-colonial era so that the state fully controls the activities of artists in one space. As a public space, Taman Ismail Marzuki cannot be separated from political intervention, which has made it an arena for contestation between artists and the state. The New Order's patrimonial practice at Taman Ismail Marzuki lasted from 1968 to 1998, allowing the state to control artists for legitimisation purposes. The questions raised in this article include: why did the state build Taman Ismail Marzuki? How did the state utilise Taman Ismail Marzuki as its political project? Who are the actors in Taman Ismail Marzuki? This article uses the historical method which includes heuristics, source criticism, interpretation and historiography. The research uses the concept of patrimonialism and departs from the concept, there are results and findings that the author describes including: (1) Patrimonialism in the Culture, (2) Negotiation Space of Politics and Culture, (3) The State Takes the Role of Culture and (4) Criticising New Order Politics.